Disciplinary practices in realising discourse functions of grammatical subjects in the result and discussion sections of research articles - Ebrahimi, Seyed Foad; Chan, Swee Heng; Abdullah, Ain Nadzimah (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study intended to scrutinize the discourse functions of the grammatical subjects used in the result and discussion section of research articles. The data for the study consist of sixteen result and discussion sections extracted from sixteen research articles published in academic journal in 2010 and 2011 from four disciplines, namely, that of English Language Teaching, Economics, Biology, and Civil Engineering (4 from each discipline). The gathered data were analyzed based on Davies’ (1988) and Gosden’s (1993) categorization of discourse functions of the grammatical subject. Findings reflected statistically significant disciplinary variations in the grammatical subjects in terms of two domains which are, participant and hypothesized and objectivized. These disciplinary variations support the claim that writers in each discipline may constraine and conditione their scientific writtings based on the discipline’s expectations, beliefs, and practices shared between the members (Lovejoy, 1991; Hyland, 1998; North, 2005). The analysis revealed how writers resort to a multiplicity of skills in realising the grammtical subject to show writing intentions in the negotiation of text development.